Report of the Task Force on the Fund's Technical Assistance Strategy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Fund technical assistance (TA) has undergone major changes during the last few years. On the demand side, there is increased interest in a longer-term, implementation-oriented TA, 'second generation' reforms, and in new topics. On the supply side, TA is increasingly financed by donors, and increasingly delivered through experts located in the field. These and other developments call for reassessing the Fund's TA strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund TA; PP; TA Delivery; TA Department; TA Provider; United States